10 and 10. - Harper, Graeme; Atherton, Cassandra; Tazelaar, Frank; Gilburt, Iona; Adsit, Janelle; Disney, Dan; Coles, Katharine; Theune, Michael; Leung, Rebecca M.L.; Vanderslice, Stephanie; Mayers, Tim (New Writing: The International Journal for the Practice & Theory of Creative Writing, 2024)
An introduction is presented in which the editor discusses articles in the issue on topics including creative writing, creative writing research, and teaching practices, celebrating the periodical's 20th anniversary with reflections from ten contributors.